Investigating Students' Reading Skill on ESP Class - Umwari, Yvette; Zulaiha, Dewi (Journal of Islamic Studies and Education, 2023)
This study aims to investigate the English reading skills of ESP students at Raden Mas Said State Islamic University Surakarta. This study uses a quantitative approach with a survey instrument as the data collection medium. A total of 127 students were involved in this study. The results show that the level of English reading ability is quite low. Furthermore, students' English reading ability can be seen from their habit of using English. Their perception of writing also shows a low level because their understanding of reading is lacking.